Pengaruh Dimensi Kualitas Pelayanan dan Kedekatan Emosional Terhadap Kepuasan Konsumen (studi kasus Ina Swiss Optik Cabang Plaza Gajah Mada Semarang) - Zainullah Achsan; Nawazirul Lubis; Widayanto Widayanto (Jurnal Ilmu Administrasi Bisnis, 2014)
In Indonesia, in line with increase of income an standard of life, push the people to more know about fashion. Line of fashion that mostly interested by people is eyewear. More request from market makes competition more strict. Then seller and distributor of eyewear must be more creative to make strategy in order to consumer satisfy with service and product quality. The strategy can be with increase dimension of service quality and more build closeness emotion to the consumers.This study aimed to determine the effect of dimension of service quality and emotion closeness toward consumer satisfaction on consumer Ina Swiss Optic Branch Plaza Gajah Mada Semarang. Population is consumer Ina Swiss Optic Branch Plaza Gajah Mada Semarang period November 2011- Oktober 2012, as the Slovin’s theory,  sample set by 96 people with spreading use of Probability Sampling methods (simple random sampling). Collecting data using interviews with the help of questionnaires that have been through the instrument validity and reliability. Data were analyzed with qualitative and quantitative analysis using the coefficient of correlation test, coefficient of determination test, simple and multiple linear regression and tests of significance with SPSS 16.0.The results showed that tangible influence consumer satisfaction of 66.7%. Reliability influence consumer satisfaction of 63.5%.Responsiveness influence consumer satisfaction of 22,9%. Assurance influence consumer satisfaction of 27.9%. Empathy influence consumer satisfaction of 33,4%. Variable emotion closeness influence consumer satisfaction of 45.6%. Simultaneously all the variables affect consumer satisfaction of 74.2%.The conclusion is the dimension of service quality and emotional closeness have positively and significant impact on consumer satisfaction at Ina Swiss Optic branch Plaza Gajah Mada Semarang as evidenced from the results of the test f count (46.619) > f table (2.199). If six factors are synergically balanced, Ina Swiss Optic will get a high level of consumer satisfaction will positively impact  in company  sustainability.